HPTLC analysis of ternary mixture containing ketorolac tromethamine, phenylephrine hydrochloride, and chlorpheniramine maleate. Issue 19 (13th December 2016) - El Yazbi, Fawzy A.; Hassan, Ekram M.; Khamis, Essam F.; Ragab, Marwa A. A.; Hamdy, Mohamed M. A.
ABSTRACT: Validated and selective high-performance thin-layer chromatography (HPTLC) method was developed for the determination of ketorolac tromethamine (KTC), phenylephrine hydrochloride (PHE), and chlorpheniramine maleate (CPM) in bulk drug and in combined dosage form. The proposed method depends on using HPTLC for separation of the drugs followed by densitometric measurements of their spots at 261 nm. The separation was carried out on Merck HPTLC aluminum sheets of silica gel 60 F254 using chloroform–methanol–ammonia (7.75:2.25:0.1, v/v) as mobile phase. Linear regression lines were obtained over the concentration ranges 0.12–0.50, 0.075–0.27, and 0.09–0.27 µg band −1 for KTC, PHE, and CPM, respectively, with correlation coefficients higher than 0.999. The method was successfully applied to the analysis of the three drugs in their synthetic mixtures and in their dosage form. The mean percentage recoveries were in the range of 98–102% with percentage relative standard deviation values less than 2%. The method was validated according to ICH guidelines and showed good performances in terms of linearity, precision, accuracy, sensitivity, and stability. GRAPHICAL ABSTRACT: